Seedling Regeneration in the Alpine Treeline Ecotone: Comparison of Wood Microsites and Adjacent Soil Substrates - Adelaide Chapman Johnson; J. Alan Yeakley (Mountain Research and Development, 2016)
Although climate warming is generally expected to facilitate upward advance of forests, conifer seedling regeneration and survival may be hindered by low substrate moisture, high radiation, and both low and high snow accumulation. To better understand substrate-related factors promoting regeneration in the alpine treeline ecotone, this study compared 2 substrates supporting conifer seedlings: rotten downed wood and adjacent soil. Study locations, each with 3 levels of incoming radiation, were randomly selected at forest line–alpine meadow borders in Pacific Northwest wilderness areas extending along an east–west precipitation gradient. Associations among substrate type, seedling density, radiation, site moisture, site temperature, plant water potential, and plant stomatal conductance were assessed. Wood microsites, flush with the ground and supporting Abies spp conifer seedlings, extended up to 20 m into alpine meadows from the forest line. Although wood microsites thawed later in the spring and froze earlier in the fall, they had warmer summer temperatures, greater volumetric water content, and more growing degree hours, and seedlings growing on wood had higher water potentials than seedlings growing on adjacent soil. At drier eastern sites, there was a positive relationship between seedling density and volumetric water content. Further, there was a positive relationship between seedling stomatal conductance and volumetric water content. Our study indicates that in the Pacific Northwest. and likely elsewhere, seedlings benefit from wood microsites, which provide greater water content. Given predictions of increased summer drought in some locations globally, wood microsites at forest line–alpine meadows and forest line–grasslands borders may become increasingly important for successful conifer regeneration.